Cooling of animal products in an air-gas environment of carbon dioxide - Aldamatov N. E.; Bredihin S. A.; Neverov E. N. (Vestnik MGTU)
In our country, as well as throughout the world, special attention is paid to finding more modern, energy-efficient and environmentally friendly methods of cooling food products, including animal ones. The basis of most technological processes of refrigeration treatment is working fluids, which can be natural or synthetic substances. Due to the negative impact of synthetic raw materials on the environment, preference is given to substances of natural origin. The greatest interest in the last twenty years in the world community of refrigeration equipment and technology is shown to carbon dioxide. This refrigerant is actively used in traditional vapor-compression refrigeration machines. In Russia carbon dioxide as a working substance in closed cycles of refrigeration machines is found at industrial facilities whose operation is based on cascade cycles. In this case, carbon dioxide acts as a working substance of the lower cascade, since it belongs to high-pressure refrigerating agents. Until 2022, carbon dioxide-based refrigerants were also actively developed at transcritical temperature levels, where the condensation temperature of carbon dioxide is close to ambient temperatures. In this study, carbon dioxide will be considered as a refrigerant when it interacts with the product in an air-gas environment during sublimation, in which carbon dioxide changes its aggregate state from snow-like to gaseous.